Improving Student Learning Concentration in Chemistry Using the ‘Everyone Is a Teacher Here’ Strategy Assisted by Genially Media - Elferida Sormin; Nova Irawati Simatupang; Sumiyati Sumiyati; Dera Savera (Postgraduate, University of Mataram, 2025)
Student concentration in learning chemistry tends to be low due to the abstract nature of the material and the dominance of teacher-centered approaches. Innovative, student-centered strategies and interactive media are needed to enhance engagement and focus. This study aims to investigate the improvement of student learning concentration through the